DIGITALISASI ANGGARAN DAERAH UNTUK SUKSES PEMILU 2024 DI KABUPATEN BOJONEGORO - Dian Wijaya (MAJAPAHIT POLICY, 2025)
Technology advances year by year. The Election Organizers (KPU) utilizes the ever-evolving sophistication of information technology by developing the Information System for Members of the General Election Commission and Ad Hoc Bodies (SIAKBA). Implementing the recruitment process for Sub-district Election Committees and Voting Committees as stipulated in KPU Regulation Number 8 of 2022 concerning the Establishment and Work Procedures of Ad-hoc Bodies in the implementation of the 2024 Election. This study aims to determine how SIAKBA is implemented in the recruitment of Ad-hoc bodies at the sub-district and village levels. The method used in this study is a qualitative method with a descriptive approach. Data collection techniques were obtained from the field (interviews, observation, and documentation). From the results of the study using George Edward's theory, it was concluded that the Bojonegoro Regency KPU is ready to carry out the recruitment of Ad-hoc bodies for PPK and PPS members through SIAKBA. Through excellent communication patterns, highly supportive resources, the disposition or attitude of the SIAKBA team in accepting applicants is full of commitment, responsibility, and ready to carry out all stages of recruitment based on applicable rules and norms.